Overview X Swimming Pool Sanitation In Banyuwangi - Dwi Lailatul Fitria; Nur Risca Azizah; Rizka Khawari; Faris Mohammad Hadi; Septa Indra Puspikawati (Universitas Airlangga, 2019)
Pool sanitation needs to be monitored and monitored against the physical environment that affects human health in order to prevent the occurrence of transmission and source of disease in the pool. The swimming pool business standard is set in the Minister of Tourism of Republic of Indonesia Regulation No. 16 of 2015. Based on SWOT analysis conducted by the researchers, the position of swimming pool X in Banyuwangi is in quadrant IV. The purpose of this research is to know the description of sanitation of swimming pool X in Banyuwangi. This research uses observational method which analyzed with descriptive. The time of the research on June 3, 2016 took place in the swimming pool X Banyuwangi. Observations were performed using a research instrument. The research instrument contains 5 variables ie place, building, swimming pool, supporting facilities and infrastructure facilities. Intrumen is prepared based on the Minister of Health Regulation No. 61 of 1991 that has been processed. The results showed the total value of place variables (3.45), building variables (3.6), pool variables (6.6), supporting facilities (6.0), and infrastructure (2.2) swimming pool X in Banyuwangi is in good condition with value 82,7% (21,85). Suggestions for pool manager X in Banyuwangi to separate chemical warehouse with First Aid Equipment (P3K) equipment and hygiene kits such as broom, waste shovel, sprinkler of swimming pool filtration, vacuum equipment and others.